Method for preparing chromium alloy cast iron mother liquor from laterite nickel ore high-pressure acid leaching residue by short process
Patent Information
- Application Number
- CN202611467585.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]针对现有技术中对于HPAL渣中铬资源回收难度大,铬资源化利用率低等技术问题,本发明的目的旨在提供一种红土镍矿高压酸浸渣短流程制取铬合金铸铁母液的方法,该方法采用“空气焙烧、预还原及深度还原熔分”的工艺流程,以实现HPAL渣中铁和铬资源的协同共回收,且最终的炉渣可以作为建筑材料原料,大大提高了HPAL渣的资源化利用率
[0023]本发明针对HPAL渣采用了“空气焙烧、预还原及深度还原熔分”的工艺流程,以实现HPAL渣中铁和铬资源的协同共回收,且最终的炉渣可以作为建筑材料原料,大大提高了HPAL渣的资源化利用率,解决了现有技术中HPAL渣中铬资源回收难度大,铬资源化利用率低等技术问题。
Smart Images

Figure CN123005129A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for the resource utilization of high-pressure acid leaching residue from laterite nickel ore, and particularly to a method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue from laterite nickel ore in a short process, belonging to the field of comprehensive utilization technology of metallurgical solid waste. Background Technology
[0002] With the rapid development of industries such as new energy vehicles and energy storage batteries, the demand for nickel resources continues to grow. Currently, due to the depletion of sulfide nickel ore resources and the continuous deterioration of economic exploitability, laterite nickel ore, which is abundant in resources and easy to mine, has become an important source for future nickel resource development and utilization. Among them, limonite-type laterite nickel ore accounts for as much as 61% of laterite nickel ore resources and has become an important source of raw materials for hydrometallurgical nickel extraction.
[0003] High-pressure acid leaching (HPAL) of laterite nickel ore has become the mainstream technology for the industrial development and utilization of this type of resource due to its significant advantages, such as high nickel and cobalt leaching rates and flexible product solutions, as well as its ability to economically and efficiently process low-grade limonite-type laterite nickel ore. However, during HPAL production, approximately one hundred tons of HPAL slag are typically generated for every ton of metallic nickel produced. Currently, HPAL slag is mainly disposed of through stockpiling or landfilling, which not only occupies a large amount of land resources and increases the treatment costs for enterprises, but also poses environmental risks such as acidic leachate and heavy metal leaching during long-term stockpiling, becoming a key bottleneck restricting the green and sustainable development of the HPAL process.
[0004] In recent years, extensive research has been conducted on the resource utilization of HPAL slag, mainly involving building materials, battery materials, environmental functional materials, and metallurgical furnace feedstocks. While building materials can achieve a certain scale of solid waste disposal, they primarily focus on the material application of the slag itself, making it difficult to recover valuable elements such as iron and chromium. Battery materials and environmental functional materials have high added value, but are limited by process costs and market demand, making it difficult to meet the needs of large-scale HPAL slag utilization. In contrast, utilizing HPAL slag as a furnace feedstock, which combines the potential for large-scale disposal and the recovery of valuable elements, is an important approach to achieving its resource utilization. However, existing technologies primarily focus on iron resource recovery, with insufficient attention paid to the synergistic enrichment and recovery of chromium in the slag. For example, Chinese patent application (CN119351726A) discloses a process where sulfur-containing iron slag is dried, crushed, graded, and briquetted. The resulting briquettes are then fed onto a belt roasting machine trolley for sequential forced-air drying, forced-air drying, roasting, homogenization, and cooling to obtain roasted briquettes. During roasting, flue gas with a sulfur dioxide volume concentration >1.0% is collected separately for sulfuric acid production, and the roasted briquettes are used for iron ore agglomeration or as raw material for iron smelting. Since chromium in HPAL slag is mainly found in chromite and iron oxide phases, recovery is difficult. In existing processes, only a small amount of chromium enters the metal product, with most remaining in byproducts such as smelting or beneficiation tailings, leading to insufficient utilization of chromium resources and increasing the difficulty of subsequent tailings treatment. Summary of the Invention
[0005] To address the technical problems of high difficulty in recovering chromium resources from HPAL slag and low chromium resource utilization rate in existing technologies, the present invention aims to provide a short-process method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching slag of laterite nickel ore. This method adopts a process flow of "air roasting, pre-reduction and deep reduction smelting" to achieve synergistic recovery of iron and chromium resources from HPAL slag, and the final slag can be used as a raw material for building materials, which greatly improves the resource utilization rate of HPAL slag.
[0006] To achieve the above-mentioned technical objectives, the present invention provides a short-process method for producing chromium alloy cast iron mother liquor from laterite nickel ore high-pressure acid leaching slag, which includes the following steps:
[0007] (1) The high-pressure acid leaching residue of laterite nickel ore is pressed into briquettes and then roasted in air at a temperature of 1100-1300℃ to obtain roasted briquettes;
[0008] (2) The calcined block is mixed with a carbonaceous reducing agent and pre-reduced at a temperature of 950~1200℃ to obtain a pre-reduced block;
[0009] (3) The pre-reduced block is subjected to deep reduction melting at a temperature of 1500℃~1700℃ to obtain chromium alloy cast iron mother liquor and slag.
[0010] Addressing the challenge that chromium in HPAL slag primarily exists as a stable chromite spinel phase, making direct reduction difficult, this invention focuses on employing a "air roasting, pre-reduction, and deep reduction smelting" technique. This technique aims to reconstruct the chromite spinel phase and efficiently reduce iron and chromium, ultimately yielding chromium alloy cast iron mother liquor. This achieves the synergistic recovery of iron and chromium resources from HPAL slag, significantly improving its resource utilization rate. Before reducing HPAL slag agglomerates, this invention involves air roasting. During air roasting, high temperatures and an oxidizing atmosphere are used to promote the reduction of Fe in the chromite spinel phase. 2+ To Fe 3+ The transformation disrupts the stability of its crystal structure, causing cracks and a loose structure in its particles, significantly increasing the activity of subsequent reduction reactions. Simultaneously, during air roasting, the deep removal and decomposition of sulfur-containing phases in the slag can be achieved, reducing the adverse effects of sulfur on the performance of subsequent iron-chromium alloyed products and providing favorable conditions for obtaining high-quality chromium alloy cast iron mother liquor. The roasted blocks obtained from air roasting achieve synergistic enrichment of iron and chromium and generate chromium alloy cast iron mother liquor through a "pre-reduction-deep reduction melting" coupling process. In the pre-reduction stage, the main phase of hematite is moderately converted into metallic iron and low-valence iron oxides, significantly reducing the iron oxide reduction load in the subsequent deep reduction melting stage of the submerged arc furnace. At the same time, pre-reduction controls the iron metallization rate within a suitable range, avoiding excessive reduction that could cause mismatch in the furnace charge's resistance characteristics, thus providing favorable conditions for efficient and low-energy-consumption smelting in the submerged arc furnace. Furthermore, the pre-reduction block undergoes deep reduction and melting, which promotes the deep reduction of chromium oxides and completes the reduction of residual iron oxides through high-temperature reduction and melting. This enriches iron and chromium elements into the liquid metal phase, ultimately yielding chromium alloy cast iron mother liquor with iron and chromium recovery rates of not less than 90% and 85%, respectively.
[0011] As a preferred embodiment, the molding pressure used for the briquette is 10–25 MPa. Controlling the molding pressure within a suitable range ensures the quality and mechanical strength of the briquette.
[0012] As a preferred embodiment, the size of the raw briquettes obtained by the pressing is 5-28 mm. When the briquettes are too large, the internal heat transfer and gas diffusion resistance increases, reducing the pre-reduction efficiency; when the briquettes are too small, the pressure drop of the material layer is easily increased, which deteriorates the permeability during the melting process and affects the slag-gold separation and the overall process stability.
[0013] As a preferred embodiment, the roasting time is 10–50 min. Within the preferred roasting temperature and time range, the phase reconstruction of chromite spinel can be promoted, resulting in cracks and a loose structure in its particles, significantly improving the activity of subsequent reduction reactions. It can also promote the decomposition of sulfur-containing phases in the acid leaching residue, achieving effective desulfurization, while simultaneously improving the agglomerate strength. If the roasting temperature is too low or the time is insufficient, the conversion of chromite spinel is likely to be incomplete, reducing chromium recovery, and resulting in insufficient desulfurization and insufficient strength of the roasted blocks. If the roasting temperature is too high or the time is too long, the porosity of the roasted blocks is likely to decrease, affecting gas diffusion and mass transfer efficiency in the subsequent reduction process. Therefore, by controlling the roasting temperature and time conditions, roasted blocks with low sulfur content, high strength, and good mass transfer performance can be obtained.
[0014] As a preferred embodiment, the calcined block has a compressive strength of not less than 500 N / piece, a sulfur content of not more than 0.08 wt%, and a porosity of 20% to 45%.
[0015] As a preferred embodiment, during the pre-reduction process, the amount of carbonaceous reducing agent added is measured according to a mass ratio of carbon in the reducing agent to iron in the calcined block of 0.4 to 1.0. If the C / Fe ratio is too low, it is easy to cause insufficient reduction of iron oxides; if the C / Fe ratio is too high, it will increase the consumption of reducing agent and may affect the subsequent melting process.
[0016] As a preferred embodiment, the carbonaceous reducing agent is at least one of bituminous coal, lignite, semi-coke, and biochar.
[0017] As a preferred embodiment, the carbonaceous reducing agent has a fixed carbon content of 50–80 wt%, a volatile matter content of 10–35 wt%, an ash content not exceeding 15 wt%, a total sulfur content not exceeding 1.0 wt%, and a particle size of 5–25 mm. A suitable fixed carbon content and volatile matter composition in the carbonaceous reducing agent balances reducing capacity and reactivity. If the fixed carbon content is too low, the reducing capacity is insufficient and the reducing agent consumption needs to be increased; if the volatile matter content is too low, it is not conducive to the pre-reduction reaction; if the ash content is too high, it is easy to induce a low-melting-point liquid phase, or even the risk of "ring formation". If the sulfur content is too high, it is easy to affect the quality of the alloy product.
[0018] As a preferred embodiment, the pre-reduction time is 0.5~3 hours. By controlling the temperature and time of the pre-reduction treatment, the reduction rate of iron oxides can be controlled, the released reduction rate reduces the reduction load in the subsequent deep reduction melting stage, and the resistance characteristics of the furnace charge are optimized. Under preferred pre-reduction conditions, the metallization rate of the pre-reduced blocks can be controlled at 35%~75%. If the pre-reduction temperature is too low or the time is insufficient, the reduction reaction will be incomplete; if the temperature is too high or the time is too long, it will easily lead to increased energy consumption and adhesion between the liquid phase agglomerates, affecting the smooth operation of the pre-reduction process.
[0019] As a preferred embodiment, the temperature of the pre-reduced block is controlled to be no lower than 600°C before deep reduction melting. The pre-reduced block is preferably introduced into the deep reduction melting process using a hot-loading method. This hot-loading method reduces heat loss during the cooling process of the pre-reduced block, improves energy efficiency, and reduces energy consumption in the deep reduction melting stage.
[0020] As a preferred embodiment, during the deep reduction melting process, the pre-reduced blocks are mixed with a regulator to form a furnace charge for deep reduction melting. The regulator is used to control the mass ratio of the effective fixed carbon to the total iron in the furnace charge (C / Fe) to be 0.12 to 0.25, and to control the quaternary basicity of the slag: mass ratio (CaO+MgO) / (SiO2+Al2O3) = 0.6 to 1.2, mass ratio MgO / Al2O3 = 0.2 to 0.8, and to control the FeO content in the furnace charge to be no higher than 2 wt%. During the deep reduction melting process, appropriate external regulators can be added as needed to control the quaternary basicity and fixed carbon content of the slag. Regulators include slag-forming regulators and carbonaceous reducing agents; slag-forming regulators include calcareous regulators and / or magnesian regulators, wherein the calcareous regulator includes at least one of limestone and lime; the magnesian regulator includes at least one of magnesite, lightly calcined magnesia, and industrial-grade MgO; composite regulators containing both calcareous and magnesian regulators can also be used, such as dolomite and calcined dolomite. During the deep reduction melting process, carbonaceous reducing agents can be added as needed based on the existing effective fixed carbon content in the pre-reduced material to adjust the total effective fixed carbon in the furnace charge. When the residual fixed carbon is insufficient to meet the C / Fe mass ratio, at least one of coke, semi-coke, anthracite, low-sulfur petroleum coke, and biochar can be added, preferably coke, semi-coke, or a combination thereof. When the C / Fe mass ratio is below 0.12, the effective fixed carbon content may be insufficient to meet the deep reduction requirements of residual iron and chromium oxides, leading to an increase in the FeO and chromium oxide content in the final slag. When the C / Fe mass ratio is above 0.25, excess carbon may exacerbate alloy carburizing and promote excessive reduction of slag components such as SiO2. Therefore, controlling the C / Fe mass ratio between 0.12 and 0.25 is beneficial for balancing deep reduction of iron and chromium, alloy composition control, and slag-metal separation.
[0021] As a preferred embodiment, the slag is used as a raw material for building materials. The slag can be used as a raw material for building materials, in the preparation of cement and cementitious materials, as well as in the production of road base materials, building aggregates, and other products. The smelting tailings contain major components such as SiO2, Al2O3, CaO, and MgO, exhibiting compositional characteristics similar to those of building material raw materials. After processing such as crushing, grinding, and iron removal, it can be used as a cement admixture, cementitious material admixture, or building aggregate, realizing the resource utilization of smelting tailings and improving the comprehensive utilization level of high-pressure acid leaching slag from laterite nickel ore.
[0022] Compared with the prior art, the beneficial technical effects of the technical solution of the present invention are as follows:
[0023] This invention employs an "air roasting, pre-reduction, and deep reduction melting" process for HPAL slag to achieve the synergistic recovery of iron and chromium resources in HPAL slag. Furthermore, the final slag can be used as a raw material for building materials, greatly improving the resource utilization rate of HPAL slag and solving the technical problems of high difficulty in recovering chromium resources from HPAL slag and low chromium resource utilization rate in existing technologies.
[0024] This invention achieves an iron recovery rate of no less than 90% and a chromium recovery rate of no less than 85% in HPAL slag.
[0025] The chromium alloy cast iron mother liquor obtained by the present invention using HPAL slag comprises, by mass percentage, Cr 1.0-10.0 wt%, C 1.0-5.0 wt%, Si not more than 2.5 wt%, S not more than 0.1 wt%, and P not more than 0.1 wt%.
[0026] The present invention provides a method for recovering iron and chromium from HPAL slag, which can then be used in the preparation of building materials, thereby enhancing the comprehensive utilization value of HPAL slag.
[0027] In summary, this invention achieves large-scale and resource-based utilization of HPAL slag, while improving the comprehensive recovery rate of valuable metals, reducing the pressure of final tailings disposal and environmental risks, and expanding its resource utilization pathways. Attached Figure Description
[0028] Figure 1 This is a process flow diagram of the present invention for preparing chromium alloy cast iron mother liquor using high-pressure acid leaching slag from laterite nickel ore.
[0029] Figure 2 The image shows the XRD pattern of the high-pressure acid leaching residue of laterite nickel ore in Example 1 of this invention.
[0030] Figure 3 SEM-EDS analysis of high-pressure acid leaching residue of laterite nickel ore before and after roasting in Example 1 of this invention; wherein, (a) is the SEM morphology of chromite in high-pressure acid leaching residue of laterite nickel ore before roasting; (b) is the SEM morphology of chromite in high-pressure acid leaching residue of laterite nickel ore after roasting; (c) is the EDS energy spectrum and elemental composition of point A in (a); (d) is the EDS energy spectrum and elemental composition of point B in (b); (e) is the EDS energy spectrum and elemental composition of point C in (b). Detailed Implementation
[0031] The following specific embodiments are only for further illustrating the content of the present invention, and are not intended to limit the scope of protection of the claims of the present invention.
[0032] Example 1
[0033] This embodiment uses the acid leaching residue produced during the high-pressure acid leaching process of limonite-type laterite nickel ore as raw material, and its XRD pattern is shown below. Figure 2 As shown, from Figure 2 As can be seen, it contains spinel-type chromite (Fe,Mg)(Cr,Al)₂O₄. The high-pressure acid leaching residue is taken from the solid residue obtained after the washing step of the high-pressure acid leaching process, and its main chemical composition is shown in Table 1. After dehydration and crushing, the obtained acid leaching residue is pressed into shape using a briquetting device at a pressing pressure of 15 MPa to obtain green lumps with dimensions of 25 mm × 25 mm × 14 mm. Subsequently, the obtained green lumps are dried and roasted in air at a temperature of 1150 °C for 40 min to obtain roasted lumps. The sulfur content of the obtained roasted lumps is 0.017 wt%, and the porosity is 29%. Using bituminous coal as the reducing agent in the pre-reduction stage, the obtained roasted lumps are pre-reduced, and the C / Fe mass ratio is controlled at 0.6. Pre-reduction is carried out at 1050 °C for 1.5 h to obtain pre-reduced lumps. Sampling and testing show that the metallization rate of the pre-reduced lumps reaches 56%. After pre-reduction, the pre-reduced blocks are separated from the unreacted bituminous coal residue. Then, using coke powder as the reducing agent in the deep reduction melting stage, along with lime and lightly calcined magnesia, the resulting pre-reduced blocks are fed into a hoist furnace for deep reduction melting. The C / Fe mass ratio is controlled at 0.20, the smelting temperature at 1600℃, and the smelting time at 60 min. The slag quaternary basicity (CaO+MgO) / (SiO2+Al2O3) is controlled at 0.8, and the MgO / Al2O3 mass ratio is controlled at 0.4. After deep reduction melting, chromium alloy cast iron mother liquor and smelting slag are obtained. Testing shows that the slag has an FeO content of 1.2%, an iron recovery rate of 94.2%, and a chromium recovery rate of 88.5%. The obtained chromium alloy cast iron mother liquor contains 5.8 wt% Cr, 3.2 wt% C, 1.6 wt% Si, 0.045 wt% S, and 0.06 wt% P.
[0034] After processing, the resulting smelting tailings have the potential to be used in the preparation of building materials, and can be used as raw materials for products such as cement and cementitious materials, road base materials or building aggregates.
[0035] Table 1. Main chemical composition (%) of acid leaching residue
[0036] SEM-EDS analysis of laterite nickel ore high-pressure acid leaching residue before and after roasting, as follows: Figure 3 As shown. Figure 3 (a) is a SEM image of the high-pressure acid leaching residue of laterite nickel ore. It can be seen from the SEM image that the chromite particles in the leaching residue have a dense structure and relatively uniform internal structure. Figure 3(c) in the image shows the EDS spot scan result of point A in the SEM image of the high-pressure acid leaching residue of laterite nickel ore: it can be seen that Cr–Fe exhibits obvious enrichment characteristics. Figure 3 Image (b) is a SEM image of the high-pressure acid leaching residue of laterite nickel ore after air roasting. The SEM image shows that a large number of interwoven needle-like or banded new phases are formed inside the grains, accompanied by loose pores, indicating that the original dense spinel structure has been significantly reconstructed. Figure 3 (d) and (e) are EDS spot scan results of points B and C in the SEM images of high-pressure acid leaching residue of laterite nickel ore after air roasting. The results show that the Cr mass fractions at points B and C are 29.25% and 30.99%, respectively. Point B is relatively enriched in Fe and Al, while point C is relatively enriched in Mg and Al, reflecting element redistribution and phase reconstruction within the particles during roasting. High-temperature oxidation promotes Fe in spinel. 2+ To Fe 3+ The transformation weakens the stability of its crystal structure; the resulting new phase and loose pores increase the reaction interface and gas diffusion channels, which is beneficial to improving the activity of subsequent reduction reactions.
[0037] Example 2
[0038] This embodiment uses high-pressure acid leaching residue from the same source as in Example 1 as the raw material. The obtained acid leaching residue was dehydrated and crushed, then pressed into briquettes using a briquetting device at a pressure of 20 MPa, yielding raw briquettes with dimensions of 25 mm × 25 mm × 14 mm. Subsequently, the raw briquettes were dried and calcined in air at a temperature of 1250 °C for 20 min to obtain calcined briquettes. Testing revealed that the sulfur content of the calcined briquettes was 0.005 wt%, and the porosity was 26%. Using bituminous coal as the reducing agent in the pre-reduction stage, the calcined briquettes underwent pre-reduction treatment, controlling the C / Fe mass ratio at 0.9. Pre-reduction was performed at 1100 °C for 1 h to obtain pre-reduced briquettes. Sampling and testing showed that the metallization rate of the pre-reduced briquettes reached 68%. After pre-reduction, the pre-reduced briquettes were separated from the unreacted bituminous coal residue. Subsequently, coke powder was used as the reducing agent in the deep reduction melting stage, along with lime and lightly calcined magnesia. The resulting pre-reduced blocks were fed into a hoist furnace for deep reduction melting treatment. The C / Fe mass ratio was controlled at 0.15, the smelting temperature at 1650℃, and the smelting time at 45 min. The slag quaternary basicity (CaO+MgO) / (SiO2+Al2O3) was controlled at 1.0, and the MgO / Al2O3 mass ratio was controlled at 0.6. After deep reduction melting, chromium alloy cast iron mother liquor and smelting slag were obtained. Testing showed that the slag had an FeO content of 0.9%, an iron recovery rate of 95.1%, and a chromium recovery rate of 90.2%. The obtained chromium alloy cast iron mother liquor contained 6.0 wt% Cr, 3.5 wt% C, 1.8 wt% Si, 0.038 wt% S, and 0.05 wt% P.
[0039] After processing, the resulting smelting tailings have the potential to be used in the preparation of building materials, and can be used as raw materials for products such as cement and cementitious materials, road base materials or building aggregates.
[0040] Comparative Example 1
[0041] This comparative example uses high-pressure acid leaching residue from limonite-type laterite nickel ore of the same source as in Example 1 as the raw material. The difference is that no roasting pretreatment is performed. The obtained acid leaching residue is dehydrated and crushed, then pressed into briquettes using a briquetting device at a pressure of 15 MPa to obtain green briquettes with dimensions of 25 mm × 25 mm × 14 mm. Bituminous coal is used as the reducing agent in the pre-reduction stage, and the dried green briquettes are directly subjected to pre-reduction treatment, controlling the C / Fe mass ratio at 0.6. Pre-reduction is carried out at 1050 °C for 1.5 h to obtain pre-reduced briquettes. Sampling and testing show that the metallization rate of the pre-reduced briquettes reaches 47%. After pre-reduction, the pre-reduced briquettes are separated from the unreacted bituminous coal residue. Subsequently, coke powder was used as the reducing agent in the deep reduction melting stage, along with lime and lightly calcined magnesia. The resulting pre-reduced blocks were fed into a hoist furnace for deep reduction melting treatment. The C / Fe mass ratio was controlled at 0.20, the smelting temperature at 1600℃, and the smelting time at 60 min. The slag quaternary basicity (CaO+MgO) / (SiO2+Al2O3) was controlled at 0.8, and the MgO / Al2O3 mass ratio was controlled at 0.4. After deep reduction melting, chromium alloy cast iron mother liquor and smelting slag were obtained. Testing showed that the slag contained 3.6% FeO, with an iron recovery rate of 90.7% and a chromium recovery rate of 61.5%. The obtained chromium alloy cast iron mother liquor contained 4.1 wt% Cr, 3.0 wt% C, 1.5 wt% Si, 0.22 wt% S, and 0.07 wt% P.
[0042] It is known that after canceling the roasting pretreatment, on the one hand, the spinel structure of chromite is not effectively activated, which reduces the efficiency of subsequent reduction reaction and leads to a decrease in the recovery rate of iron and chromium resources; on the other hand, since the sulfur-containing phase in the raw material is not removed by roasting, some sulfur enters the metal phase, resulting in an increase in the sulfur content of the obtained chromium alloy cast iron mother liquor, which is difficult to meet the composition requirements of high-quality chromium alloy cast iron mother liquor.
[0043] Comparative Example 2
[0044] This comparative example uses high-pressure acid leaching slag from limonite-type laterite nickel ore of the same source as in Example 1. The difference is that no pre-reduction treatment is performed. The obtained acid leaching slag is dehydrated and crushed, then pressed into briquettes using a briquetting device at a pressure of 15 MPa to obtain green briquettes with dimensions of 25 mm × 25 mm × 14 mm. Subsequently, the green briquettes are dried and roasted in air at a temperature of 1150 °C for 40 min to obtain roasted briquettes. Then, using coke powder as the reducing agent in the deep reduction melting stage, along with lime and lightly calcined magnesia, the roasted briquettes are directly fed into a furnace for deep reduction melting. The C / Fe mass ratio is controlled at 0.80, the smelting temperature is controlled at 1600 °C, and the smelting time is controlled at 60 min. The slag quaternary basicity (CaO+MgO) / (SiO2+Al2O3) is controlled at 0.8, and the MgO / Al2O3 mass ratio is controlled at 0.4. After deep reduction melting, chromium alloy cast iron mother liquor and smelting slag were obtained. Analysis showed that the slag contained 10.2% FeO, with an iron recovery rate of 85.6% and a chromium recovery rate of 67.3%. The obtained chromium alloy cast iron mother liquor contained 4.5 wt% Cr, 1.7 wt% C, 1.5 wt% Si, 0.052 wt% S, and 0.06 wt% P.
[0045] It can be seen that after the pre-reduction treatment is cancelled, a large amount of iron oxides need to be reduced in the deep reduction melting stage, which increases the reduction load in the high-temperature melting process, resulting in a decrease in the reduction and enrichment efficiency of iron and chromium elements, and a significantly lower recovery rate of iron and chromium elements.
[0046] Comparative Example 3
[0047] This comparative example uses high-pressure acid leaching residue from limonite-type laterite nickel ore of the same source as in Example 1 as the raw material. The difference lies in the unsuitable smelting temperature during the deep reduction melting stage. The obtained acid leaching residue was dehydrated and crushed, then pressed into briquettes using a briquetting device at a pressure of 15 MPa, yielding green briquettes with dimensions of 25 mm × 25 mm × 14 mm. Subsequently, the green briquettes were dried and roasted in air at a temperature of 1150°C for 40 minutes to obtain roasted briquettes. Testing revealed that the sulfur content of the roasted briquettes was 0.017 wt%, and the porosity was 29%. Using bituminous coal as the reducing agent in the pre-reduction stage, the roasted briquettes underwent pre-reduction treatment, controlling the C / Fe mass ratio at 0.6. Pre-reduction was carried out at 1050°C for 1.5 hours to obtain pre-reduced briquettes. Sampling and testing showed that the metallization rate of the pre-reduced briquettes reached 56%. After pre-reduction, the pre-reduced briquettes were separated from the unreacted bituminous coal residue. Subsequently, coke powder was used as the reducing agent in the deep reduction melting stage, along with lime and lightly calcined magnesia. The resulting pre-reduced blocks were fed into a hoist furnace for deep reduction melting treatment. The C / Fe mass ratio was controlled at 0.20, the smelting temperature at 1450℃, and the smelting time at 60 min. The slag quaternary basicity (CaO+MgO) / (SiO2+Al2O3) was controlled at 0.8, and the MgO / Al2O3 mass ratio was controlled at 0.4. After deep reduction melting, chromium alloy cast iron mother liquor and smelting slag were obtained. Testing showed that the obtained slag had an FeO content of 8.6%, an iron recovery rate of 88.9%, and a chromium recovery rate of 40.1%. The obtained chromium alloy cast iron mother liquor contained 2.7 wt% Cr, 2.3 wt% C, 0.8 wt% Si, 0.062 wt% S, and 0.06 wt% P.
[0048] It is known that a lower smelting temperature is not conducive to the full melting of the furnace charge and slag, and weakens the reduction of residual iron and chromium oxides, as well as the aggregation, growth and sedimentation separation of molten metal droplets, resulting in an increase in the residual amount of FeO and chromium oxides in the final slag and a decrease in the recovery rate of iron and chromium.
[0049] Comparative Example 4
[0050] This comparative example uses high-pressure acid leaching slag from limonite-type laterite nickel ore of the same source as in Example 1. The difference lies in the unsuitable control of the slag regime during the deep reduction melting stage. The obtained acid leaching slag is dehydrated and crushed, then pressed into briquettes using a briquetting device at a pressure of 15 MPa, yielding green briquettes with dimensions of 25 mm × 25 mm × 14 mm. The green briquettes are then dried and roasted in air at 1150°C for 40 minutes to obtain roasted briquettes. Testing revealed that the roasted briquettes had a sulfur content of 0.017 wt% and a porosity of 29%. Bituminous coal is used as the reducing agent in the pre-reduction stage, and the roasted briquettes are pre-reduced, with the C / Fe mass ratio controlled at 0.6. Pre-reduction is performed at 1050°C for 1.5 hours to obtain pre-reduced briquettes. Sampling and testing showed that the metallization rate of the pre-reduced briquettes reached 56%. After pre-reduction, the pre-reduced briquettes are separated from the unreacted bituminous coal residue. Subsequently, coke powder was used as the reducing agent in the deep reduction melting stage, along with lime and lightly calcined magnesia. The resulting pre-reduced blocks were fed into a hoist furnace for deep reduction melting treatment. The C / Fe mass ratio was controlled at 0.20, the smelting temperature at 1600℃, and the smelting time at 60 min. The slag quaternary basicity (CaO+MgO) / (SiO2+Al2O3) was controlled at 0.3, and the MgO / Al2O3 mass ratio was controlled at 0.1. After deep reduction melting, chromium alloy cast iron mother liquor and smelting slag were obtained. Testing showed that the obtained slag had an FeO content of 7.8%, an iron recovery rate of 85.6%, and a chromium recovery rate of 64.3%. The obtained chromium alloy cast iron mother liquor contained 4.4 wt% Cr, 3.1 wt% C, 1.7 wt% Si, 0.05 wt% S, and 0.065 wt% P.
[0051] It is known that excessively low quaternary basicity and MgO / Al2O3 mass ratio are not conducive to the depolymerization of the silicon-oxygen network structure in slag and the improvement of high-temperature flow properties, thereby hindering the aggregation, growth and slag-metal separation of metal droplets, increasing the residual amount of iron and chromium oxides in the slag, and resulting in a decrease in iron and chromium recovery rate.
Claims
1. A method for producing chromium alloy cast iron mother liquor from laterite nickel ore high-pressure acid leaching residue using a short-process method, characterized in that: Includes the following steps: (1) The high-pressure acid leaching residue of laterite nickel ore is pressed into briquettes and then roasted in air at a temperature of 1100℃~1300℃ to obtain roasted briquettes; (2) The calcined block is mixed with a carbonaceous reducing agent and pre-reduced at a temperature of 950℃~1200℃ to obtain a pre-reduced block; (3) The pre-reduced block is subjected to deep reduction melting at a temperature of 1500℃~1700℃ to obtain chromium alloy cast iron mother liquor and slag.
2. The method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 1, is characterized in that: The molding pressure used for the briquette is 10-25 MPa; The size of the raw lumps obtained by pressing is 5-28 mm.
3. The method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 1, is characterized in that: The roasting time is 10 to 50 minutes.
4. A method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 1 or 3, characterized in that: The calcined block has a compressive strength of not less than 500 N / piece, a sulfur content of not more than 0.08 wt%, and a porosity of 20% to 45%.
5. The method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 1, is characterized in that: During the pre-reduction process, the amount of carbonaceous reducing agent added is measured according to a mass ratio of carbon in the carbonaceous reducing agent to iron in the calcined block of 0.4 to 1.
0.
6. The method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 5, is characterized in that: The carbonaceous reducing agent is at least one of bituminous coal, lignite, semi-coke, and biochar; The carbonaceous reducing agent has a fixed carbon content of 50-80 wt%, a volatile matter content of 10-35 wt%, an ash content of no more than 15 wt%, a total sulfur content of no more than 1.0 wt%, and a particle size of 5-25 mm.
7. The method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 1, is characterized in that: The pre-reduction time is 0.5~3.0h.
8. The method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 1, is characterized in that: Before the pre-reduction block undergoes deep reduction melting, its temperature is controlled to be no lower than 600°C.
9. The method for producing chromium alloy cast iron mother liquor from laterite nickel ore high-pressure acid leaching residue using a short-process method, as described in claim 1, is characterized in that: During the deep reduction melting process, the pre-reduced blocks are mixed with a regulator to form a furnace charge for deep reduction melting. The regulator is used to control the mass ratio of effective fixed carbon to total iron in the furnace charge (C / Fe) to be 0.12 to 0.25, and to control the quaternary basicity of the slag: mass ratio (CaO+MgO) / (SiO2+Al2O3) = 0.6 to 1.2, mass ratio MgO / Al2O3 = 0.2 to 0.8, and to control the FeO content in the furnace charge to be no higher than 2 wt%.
10. The method for producing chromium alloy cast iron mother liquor from high-pressure acid leaching residue of laterite nickel ore using a short-process method, as described in claim 1, is characterized in that: The slag is used as a raw material for building materials.
Citation Information
Patent Citations
Method for comprehensively recovering iron and sulfur from sulfur-containing iron slag
CN119351726A
